Design of a non-isolated single phase online ups topology with parallel battery bank for low power applications / Muhammad Aamir - Muhammad , Aamir (2016)
Uninterruptible Power Supplies (UPS) are widely used to provide reliable and high quality power to critical loads such as airlines computers, datacenters, communication systems, and medical support systems in hospitals in all grid conditions. Online UPS system is considered to be the most preferable UPS due to its highest level of power quality and proven reliability against all types of line disturbances and power outages. This research presents a new topology of the non-isolated online uninterruptible power supply system. The proposed system consists of bridgeless boost rectifier, battery charger/discharger, and an inverter. The rectifier performs power factor correction and provides regulated DC-link voltage. The rectifier operates with a minimum semiconductor device, reducing the conduction losses of the circuit significantly. A new battery charger/discharger has been implemented, which ensures the bidirectional power flow between the DC-link and the battery bank, reducing the battery bank voltage to only 24V, and regulates the DC-link voltage during battery mode. The bidirectional operation of the converter is achieved by employing only three active switches, a coupled inductor, and an additional voltage clamped circuit. Batteries are connected in parallel depending on the backup time requirement of the system. Operating batteries in parallel improve the battery performance and resolve the problems related to conventional battery banks that arrange batteries in series. The inverter provides a regulated output voltage to the load. A new cascaded slide mode and proportional-resonant control have been proposed. Slide mode control is recognized as the most robust control with high stability while the proportional-resonant control shapes the output waveform closely according to the reference sinusoidal signal. Keeping in view the characteristics of slide mode and proportional-resonant control, a cascaded controller is proposed for the bipolar single-phase UPS inverter. The outer voltage loop uses the proportional-resonant control while the inner loop uses the slide mode control. The proposed control scheme regulates the output voltage for both linear and non-linear load and shows excellent performance during transients and step changes in load. The proposed controller shows significant improvement in terms of reducing the total harmonics distortion to 0.5% for linear load and 1.25% for non-linear load, strong robustness, and fast response time of only 0.3ms. Operation principle and experimental results of 1kVA prototype have been presented to verify the validity of the proposed UPS. The efficiency of the proposed system is 94% during battery mode and 92% during the normal mode of operation.